Hubungan teman sebaya dengan tingkat pengetahuan bullying di MI Daroyissalam kertosono Kecamatam Sidayu Kabupaten Gresik: Hubungan Teman Sebaya Dengan Tingkat Pengetahuan Bullying Di MI Daroyissalam Kertosono Kecamatan Sidayu Kabupaten Gresik - Jannah, Rif (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Bullying is aggressive or threatening behavior that is deliberately repeated by a person or group, which can be called harassment. This study aims to determine the relationship between peer relationships and the level of knowledge of bullying in MI Daroyissalam, Kertosono Village, Sidayu District, and Gresik Regency. The research design used correlational analytics with a cross-sectional approach. The population was 48 respondents; using the total sampling technique, we obtained 48 respondents. This research data was taken using a peer questionnaire and level of knowledge about bullying. After tabulating the data, it was analyzed using Spearman rho' test with p ˂ 0.05. The results showed that almost all students (93.75%) had good peer categories, and most students (62.5%) already had a good level of knowledge about bullying. Based on the above results of the relationship between peers and the level of knowledge about bullying, p = 0.006 (p ˂ 0.05). This means that there is a relationship between peers and their level of knowledge about bullying. Recommendations: Health workers should provide health care, especially related to behavior about bullying and the importance of having good and healthy peer relationships.